A Review on Current COVID-19 Vaccines and Evaluation of Particulate Vaccine Delivery Systems - Sarthak M. Shah; Hashem O. Alsaab; Mutasem M. Rawas-Qalaji; Mohammad N. Uddin (Vaccines, 2021)
First detected in Wuhan, China, a highly contagious coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), also known as COVID-19, spread globally in December of 2019. As of 19 September 2021, approximately 4.5 million people have died globally, and 215 million active cases have been reported. To date, six vaccines have been developed and approved for human use. However, current production and supply capabilities are unable to meet global demands to immunize the entire world population. Only a few countries have been able to successfully vaccinate many of their residents. Therefore, an alternative vaccine that can be prepared in an easy and cost-effective manner is urgently needed. A vaccine that could be prepared in this manner, as well as can be preserved and transported at room temperature, would be of great benefit to public health. It is possible to develop such an alternative vaccine by using nano- or microparticle platforms. These platforms address most of the existing vaccine limitations as they are stable at room temperature, are inexpensive to produce and distribute, can be administered orally, and do not require cold chain storage for transportation or preservation. Particulate vaccines can be administered as either oral solutions or in sublingual or buccal film dosage forms. Besides improved patient compliance, the major advantage of oral, sublingual, and buccal routes of administration is that they can elicit mucosal immunity. Mucosal immunity, along with systemic immunity, can be a strong defense against SARS-CoV-2 as the virus enters the system through inhalation or saliva. This review discusses the possibility to produce a particulate COVID vaccine by using nano- or microparticles as platforms for oral administration or in sublingual or buccal film dosage forms in order to accelerate global vaccination.